Buddhism, tourism, and development in the trans-Himalayan Buddhist region: three decades after Ancient Futures (Norberg-Hodge, 1991). (30th April 2023) - Suh, Jungho
Ladakh (India) and Bhutan opened their gates to foreign tourists in 1974. The book Ancient Futures, published in 1991 in English, depicted that the traditional Buddhist economy was being phased out while the regional economy became heavily dependent on tourism. This study critically discusses whether Buddhism, tourism, and economic development are compatible with one another in the contemporary trans-Himalayan Buddhist region, from a tourist researcher perspective. This study finds that rural villagers in both Ladakh and Bhutan do not directly reap their well-deserved benefits from tourism although they are the primary provider of rural and cultural tourism. The traditional trans-Himalayan way of life should globally be considered a plausible pathway to sustainable futures. In this context, the study suggests that community-based cultural ecotourism schemes be established in such a way to promote small-scale and place-based economic development.